Development of an energy monitoring and targeting methodology for the most efficient operation of chilled water systems : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Energy Management at Massey University, Palmerston North, New Zealand - Vaino, Federica (Massey University, 2008)
The increasing price of oil and the destabilisation of the world’s climate are urging governments, businesses and individuals to constantly investigate energy-efficient technologies and methodologies and pursue the adoption of energy efficiency programmes in a global effort to reduce energy consumption, greenhouse gas emissions and ultimately energy costs. In New Zealand, one of the biggest industrial energy efficiency projects was started in 2002 by a multinational dairy company, the Fonterra Co-operative Group, in partnership with the energy service company Demand Response Ltd; the project currently aims at reducing by 15% the energy costs at all Fonterra’s major production sites throughout the country. This thesis, undertaken as part of the above project, examines the development and implementation of a structured and integrated energy monitoring and targeting methodology (M&T) for the most efficient operation of all Fonterra’s chilled water systems, with an initial focus on the ones installed at Clandeboye, one of the Fonterra’s sites involved in the energy saving project. A data collection system (Insite) was already in place at Clandeboye to enable storage and analysis of some of the site’s utility metering data. After identification of key chilled water system components and definition of data requirements for M&T purposes, an analysis of past energy consumption trends (based on multiple regression calculations) was carried out to develop an historical benchmark of the energy used, compare it with current energy performance and thus identify opportunities for future improvements. The creation of an M&T reporting system for presenting findings to operators and management was the last essential part of the thesis development. The study has highlighted that the robustness of the proposed regression model was badly affected by the unreliability of the existing data collection system and the uncertainty associated with poorly documented changes to operating conditions/plant configuration that had occurred over time. The conclusion is that, while the developed M&T methodology is theoretically valid and readily applicable, further developments are necessary (and recommended) to make it suitable for other similar systems.
Keywords: Dairy processing; Industrial refrigeration; Chilled water systems; Energy monitoring and targeting methodology; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences